Macroprolactinoma causing VI, X, XII cranial nerve palsies nearly 30 years after initial treatment - de Bray, Anne (Endocrinol Diabetes Metab Case Rep, 2018)
A 48-year-old man was diagnosed with a large macroprolactinoma in 1982 treated with surgery, adjuvant radiotherapy and bromocriptine. Normal prolactin was achieved in 2005 but in 2009 it started rising. Pituitary MRIs in 2009, 2012, 2014 and 2015 were reported as showing empty pituitary fossa. Prolactin continued to increase (despite increasing bromocriptine dose). Trialling cabergoline had no effect (prolactin 191,380 mU/L). In January 2016, he presented with right facial weakness and CT head was reported as showing no acute intracranial abnormality. In late 2016, he was referred to ENT with hoarse voice; left hypoglossal and recurrent laryngeal nerve palsies were found. At this point, prolactin was 534,176 mU/L. Just before further endocrine review, he had a fall and CT head showed a basal skull mass invading the left petrous temporal bone. Pituitary MRI revealed a large enhancing mass within the sella infiltrating the clivus, extending into the left petrous apex and occipital condyle with involvement of the left Meckel’s cave, internal acoustic meatus, jugular foramen and hypoglossal canal. At that time, left abducens nerve palsy was also present. CT thorax/abdomen/pelvis excluded malignancy. Review of previous images suggested that this lesion had started becoming evident below the fossa in pituitary MRI of 2015. Temozolomide was initiated. After eight cycles, there is significant tumour reduction with prolactin 1565 mU/L and cranial nerve deficits have remained stable. Prolactinomas can manifest aggressive behaviour even decades after initial treatment highlighting the unpredictable clinical course they can demonstrate and the need for careful imaging review. LEARNING POINTS: Aggressive behaviour of prolactinomas can manifest even decades after first treatment highlighting the unpredictable clinical course these tumours can demonstrate. Escape from control of hyperprolactinaemia in the absence of sellar adenomatous tissue requires careful and systematic search for the anatomical localisation of the lesion responsible for the prolactin excess. Temozolomide is a valuable agent in the therapeutic armamentarium for aggressive/invasive prolactinomas, particularly if they are not amenable to other treatment modalities.